(3GdSeGJ GdafjI ddJUhjQ GdQbei ceONd dJOQjS GdJUhjQ (B: s The artistic features of digital painting as an approach for teaching painting - (3TGOi CMeO eMeO YUGe GdOjfs; (3CT`Qa ESeGYjd GdYQjfi (B: s; (3Eje`Gf eMe`O GdSf`hQ (B: s ((3GdbGgQI (B: s (3TGOi CMeO eMeO YUGe GdOjf (B: s, 2015)
(3jgOa gPG GdHMK Edi GdcTa Yf GdEecGfGJ GdCSGSjI GdehLhOI HeLGd GdJUhjQ GdQbei(B: (3h cjajI JhXjagG dNOeI GdYed GdJUhjQi ef NdGd JMOjO CHQR GdJbfjGJ h GdCSGdjH GdeSJNOeI HeLGd GdJUhjQ GdQbei(B. (3jJe Pdc Yf WQjb OQGSI GdeQGMd GdJi eQ HgG GdJUhjQ GdQbej Edi Cf hUd Edi eagheg h hVYg GdMGdi(B: (3h ef NdGd GSJNdGU GHQR GdJbfjGJ h GdCSGdjH GdJTcjdjI Yf WQjb JMdjd eLehYI ef CYeGd GdJUhjQ GdQbei dYOO ef GdafGfjf GdeYGUQjf GddPjf GSJWGYhG JhXja GdEecGfGJ GdeJYOOI GdJi JJMgG GdJWHjbGJ GdQShejI HCSGdjH eNJdaI OGNd CYeGdge GdJUhjQjI(B: (3h Pdc HgOa hVY GSJQGJjLjI hGVMI dJOQjS GdJUhjQ GdQbeis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI GdfhYjI (B- (3bSe GdJQHjI GdafjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJUhjQ GdQbeis; (3GdSeGJ GdafjI ddJUhjQ GdQbeis; (3Gdaf GdQbeis